Public utility pricing and industrial decentralization in South Africa - Wallis, Joseph Lyall (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 1984)
From Introduction: 1. Background to the thesis: During the 1950' sand 1960' s it would appear that the explicit objectives of economic policy in South Africa were full employment and economic growth with some occasional emphasis on the pursuit of relative price stability. Other goals such as efficiency in resource allocation and the pursuit of an "acceptable" income distribution were at best implicit and subordinate to these objectives. This is exemplified by the fact that a number of key prices which were controlled by the authorities such as the exchange rate, interest rates and public utility tariffs were generally set at levels which were either over- or under-priced relative to factor scarcities throughout this period.
Keywords: Industrial management -- South Africa; Public utilities -- South Africa; Pricing -- South Africa; Decentralization in management -- South Africa